Renewal and Renewal-Intensity Functions with Minimal Repair. (19th March 2014) - Maghsoodloo, Saeed; Helvaci, Dilcu
Abstract : The renewal and renewal-intensity functions with minimal repair are explored for the Normal, Gamma, Uniform, and Weibull underlying lifetime distributions. The Normal, Gamma, and Uniform renewal, and renewal-intensity functions are derived by the convolution method. Unlike these last three failure distributions, the Weibull except at shapeβ = 1 does not have a closed-form function for the n -fold convolution. Since the Weibull is the most important failure distribution in reliability analyses, the approximate renewal and renewal-intensity functions of Weibull were obtained by the time-discretizing method using the Mean-Value Theorem for Integrals . A Matlab program outputs all reliability and renewal measures.